Biliary Cripple and the Spectrum of Complications following Cholecystectomy: A Case Report. (22nd September 2022) - Shrestha, Anish Kumar; Sah, Jayant Kumar; Ghimire, Bikal; Bhandari, Aashna; Shrestha, Anisha
Abstract : Bile duct injury is a complication seen during cholecystectomy. Here, we highlight the occurrence of bile duct injury (BDI) during an open cholecystectomy who underwent hepaticojejunostomy (HJ), later presenting with a stricture of HJ. Percutaneous transhepatic biliary drainage (PTBD) was performed which led to the development of hepatic artery injury.